Large Undiagnosed Acoustic Neuroma in a Pregnant Woman Submitted to Epidural Analgesia: Case Report - Lanzaro, Camile; Cavalete, Sónia; Carvalho, Beatriz; Pereira, Eduarda; Dias, Celeste (Journal of the Portuguese Society of Anesthesiology, 2020)
Brain tumour incidence during pregnancy is low and type of tumours are similar to those seen in nonpregnant women. Pregnancy may aggravate the natural history of a brain tumour, unmask a previously undiagnosed lesion or remain assymtomatic due to its unspecific symptoms. We report a case of a pregnant woman with a large occult acoustic neuroma diagnosed after presenting neurological symptoms during epidural analgesia for labour. The tumour was causing shift of the peripheral structures and compression of the brainstem and 4th ventricle. In postpartum period, the tumour was removed without complications. Preanesthetic evaluation is essential to rule out contraindications to neuroaxial analgesia or potentially neurological life-threatening conditions.